Targums and the transmission of scripture into Judaism and Christianity - Hayward, Robert, 1948- (Studies in the Aramaic Interpretation of Scripture, 2010)
This collection of seventeen previously published essays and two hitherto unpublished articles examines strategies adopted by ancient Aramaic translators of the Hebrew Bible in their attempts to transmit the meaning of Scripture to their own generations. The intricate interpretations of Targum Pseudo-Jonathan feature prominently: analysis of them suggests a date for the substance of this Targum rather earlier than is commonly assumed. The biblical exegesis of Jerome (ca. 342-420 CE) often reflects Targumic interpretation of Scripture: as well as helping to date items of Jewish interpretation, Jerome's writings also witness to continuing close contacts between Christians and Jews at a crucial stage in the history of both communities. The essays also demonstrate the relationship of the Targums both to other Rabbinic texts and to early translations of the Bible like Septuagint; the versions of Aquila, Symmachus, and Theodotion; and the Peshitta.